Molecular Genotyping of HBV by using Nested PCR-RFLP among Hepatitis B Patients in Daerah Istimewa Yogyakarta Province and Surrounding Area - Aris Haryanto; Nenny Sri Mulyani; Titis Widowati; Nastiti Wijayanti; Purnomo Hadi (Universitas Gadjah Mada, 2008)
Hepatitis B virus (HBV) can be classified into 8 genotypes, genotype A to H. Genotype of HBV is important for clinical and etiological investigations. Research for HBV genotyping, HBV transmission study using nested PCR and HBV genotyping based on RFLP using restriction enzymes have been reported. However, both of those methods have been not applied for HBV genotyping study among hepatitis B patients in endemic area, like Indonesia yet. Molecular genotyping of HBV will describe epidemiology, pathogenesis and clinical implication of HBV. Combination of nested PCR and RFLP (nested PCR-RFLP) method to determine HBV genotype in Indonesia is still less information. The objectives of study were to develop a system for HBV genotyping by nested PCR combined with RFLP (nested PCR-RFLP) method based on nucleotide sequence of surface protein encoding gene (S gene) in HBV genome and to confirm HBV genotypes which predominantly found among hepatitis B patients in Daerah Istimewa Yogyakarta Province and surrounding area. Total of 149 sera from chronic hepatitis B patients from Daerah Istimewa Yogyakarta and surrounding areas were collected for in this work. Viral DNA were extracted from sera of hepatitis B patients and used as template for first round nested PCR amplification using outer primers set. Amplicons of first round PCR were used as template for second round amplification using inner primers set. Then, amplicons of second round nested PCR were restriction digested by Sty I and Bsr I enzymes. For HBV genotyping then the restriction products were analyzed by RFLP based on restriction pattern. Results showed that the first round nested PCR amplification generated DNA fragments of whole S gene in length 1.233 bp, and in second round nested PCR amplification using inner primer set generated DNA fragments 585 bp in length. Genotype analysis for all samples using nested PCR-RFLP methods by restriction digested of Sty I and Bsr I enzymes found only 2 HBV genotypes among hepatitis B patients, namely genotype B and C. Quantification data showed that most of hepatitis B patients found infected by HBV genotype B (92,8%), genotype C (3,6%) and unidentified genotype (3,6%). Nested PCR-RFLP methods for HBV genotyping is simple and inexpensive for clinical diagnostic in large scale.